Muscle activity in tennis - Roetert, P. (2001)
The purpose of this paper is to focus on the tennis player from a physiological perspective and specifically on the muscular actions involved in each of the tennis strokes. To be able to compete effectively against progressively more elite opponents, requires higher levels of physical fitness related to such factors as strength, power, muscular endurance, flexibility, coordination and agility. Therefore, standardized testing might provide a useful addition to subjective coaching appraisals. 2 By testing junior tennis players early in their careers, physical training programs can be implemented to strengthen weaknesses and lessen the risk of injury. 3 The exercise prescription for individual players depends on a number of factors, including the initial fitness level of the player, the goals of the player, the injury history of the player, and the level of play of the participant. 4 The muscular demands of tennis, muscle involvement in the strokes and the muscle groups used are analyzed.